2013
DOI: 10.1111/ijfs.12199
|View full text |Cite
|
Sign up to set email alerts
|

Release kinetics of antioxidant compounds fromHibiscus sabdariffaL. encapsulated in gelatin beads and coated with sodium alginate

Abstract: Summary Gelatin beads containing a concentrated extract of Roselle (Hibiscus sabdariffa L.) calyx rich in polyphenolic compounds were coated with sodium alginate and ionotropically gelled using CaCl2. Single‐coated beads and double‐coated beads were obtained by this technique, and the release pattern of the loaded extract was evaluated. As a result, release pattern of these compounds fits properly to a first–order Weibull distribution equation. The release rate constant decreased linearly with the number of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Compared to protein-based carriers, combination of protein–polysaccharide carriers can improve mechanical and release properties of the delivery systems and prevent the enzymatic degradation of the proteins in gastric condition (Diaz-Bandera et al, 2013 ; Jia et al, 2016 ). In addition, many studies have shown that globular proteins, as well as whey proteins hydrolysates, have antioxidant activity.…”
Section: Needs For Microencapsulation Of Eos: Encapsulation Technologmentioning
confidence: 99%
“…Compared to protein-based carriers, combination of protein–polysaccharide carriers can improve mechanical and release properties of the delivery systems and prevent the enzymatic degradation of the proteins in gastric condition (Diaz-Bandera et al, 2013 ; Jia et al, 2016 ). In addition, many studies have shown that globular proteins, as well as whey proteins hydrolysates, have antioxidant activity.…”
Section: Needs For Microencapsulation Of Eos: Encapsulation Technologmentioning
confidence: 99%